A Review on the Modelling of Wave-Structure Interactions Based on OpenFOAM. (2022) - Huang, Luofeng; Li, Yuzhu; Benites-Munoz, Daniela; Windt, Christian Windt; Feichtner, Anna; Tavakoli, Sasan; Davidson, Josh; Paredes, Ruben; Quintuna, Tadea; Ransley, Edward; Colombo, Marco; Li, Minghao; et al.
No abstract available